Nursing and Midwifery Policy - Malawi Government: Ministry of Health (Malawi Government, 2021)
As the Ministry of Health and Population (MOHP) pursues the ultimate goal of improving health status of all Malawians, alongside the Sustainable Development Goals, improvement of nursing and midwifery services surfaces as a key commitment in attainment of these goals. As such, the Ministry considers the development of this Nursing and Midwifery Policy for the period of 2018-2023 a step towards both the advancement of nursing and midwifery services in the country, as well as the well-being of the people of Malawi. Nursing and midwifery service provision is one of the most important pillars in health care delivery. The current increase in the general burden of disease has resulted in increased numbers of patients to be cared for 24 hours a day by nurses and midwives. The current nurse - population ratio in the country is 1: 2300 a major gap that creates a risk to quality nursing and midwifery service delivery. This challenge for nurses and midwives in the country manifests itself in low staffing and large patient loads. Availability of medical equipment and supplies poses another challenge to nursing and midwifery service delivery. Considering the importance of quality in the delivery of health services, the MOHP is committed to facilitating the creation of an enabling environment for the delivery of quality nursing and midwifery services. The development of the Malawi Nursing and Midwifery Policy 2018-2023 has been done with the intention of aligning nursing and midwifery services to the current “Health Sector Strategic Plan II 2017-2022”(HSSP II), and National Health Policy, the goal of which is to promote the quality of life of all Malawians through the delivery of an Essential Health Package.. The Nursing and Midwifery Directorate will contribute towards achievement of this goal by integrating guidance on Human Resources, Administration, Practice, Research, Education, and Quality Management, inclusive of principles of Quality Assurance and total Quality Improvement in all aspects of nursing and midwifery care. Nurses and Midwives are encouraged to continue discharging their duties with commitment, dedication and professionalism. The Ministry of Health and Population; appeals to all Government, cooperating partners, and other key stakeholders in the health sector; to utilize the policy to guide and support the delivery of Nursing and Midwifery services in the country.